QUALITY MANAGEMENT OUTREACH FOR THE SUSTAINABILITY OF MICRO, SMALL, AND MEDIUM ENTERPRISES - Suryani Maryam (Sean Institute, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the cornerstone of Indonesia's economy; nonetheless, numerous entities encounter difficulties in sustaining consistent quality in their products and services. This constraint impacts client retention, competitiveness, and long-term economic viability. In July 2025, a quality management outreach program was implemented in Depok City for 35 members of the Wira Usaha Baru (WUB) initiative in response to these difficulties. The outreach sought to enhance participants' comprehension and implementation of quality management principles, encompassing standard operating procedures (SOPs), fundamental quality control methodologies, and customer feedback systems. The activity employed a participatory learning paradigm, incorporating interactive lectures, practical workshops, group discussions, and mentorship sessions. The results demonstrated a notable enhancement in participants' understanding and awareness of quality practices. Additionally, post-training self-evaluations indicated that 80% of participants commenced the implementation of SOPs, while 65% integrated customer feedback mechanisms within a week. The results corroborate earlier research indicating that quality management can enhance MSME performance. Implementing organized quality processes enhances productivity and product consistency, hence augmenting client happiness and prospective sales growth. This outreach initiative has shown that even basic, cost-effective quality interventions can have significant impacts when customized to the context and capabilities of MSMEs. Consequently, fostering quality awareness must be a fundamental component of capacity-building programs for nascent firms.